Cidadania, educação e saúde: desvelando significados atribuídos por adolescente - Santos, Poliana Fernandes Dos (2017)
This study aims to understand the meanings attributed by adolescents institutionalized in school shifts, in discussions about the themes of Education in Human Rights. In order to do so, it is based on the foundations of Cultural Historical Psychology defined as the essential theoretical contribution to the approach of promoting the development of adolescents, as well as the presuppositions of Human Rights Education. The study was based on the analysis of the Extension Actions carried out by the Mediation Project: Health and Education Interface, carried out in a Beneficent Association of charitable and philanthropic character in the city of Alfenas / MG. The project uses the methodological contributions of the intervention research, with the definition of the group of participants composed of 17 adolescents (11 boys and 6 girls) with ages ranging from 11 to 15 years. The information constructed could be organized into two axes of discussion, the first of which places meanings attributed by adolescents to the theme Citizenship, and the second, permeating the meanings that reveal a reality surrounded by elements that evidence the Vulnerability and considerably impact the constitution of physical development , Psychological and social in the studied context. As final considerations, we show that the discussion about the themes of Human Rights Education, based on the theoretical contribution of Cultural Historical Psychology, favored a space of dialogue that allowed the participation of adolescents in the process of unveiling of living conditions and social constitutions, involving A process of understanding that enables the change of reality. However, it still proves to be a challenge the appropriation of new meanings for the potential of human development that contemplate adolescents as active subjects in their realities and social constructions.